Inventory of Butterflies and Its Role to Promote Ecotourism in Northern Sindhupalchok District of Central Nepal - Khanal, Bhaiya (Journal of Natural History Museum, 2020)
Sindhupalchok is one of the largest districts of central Nepal with area occupancy of about 2542 km². The northern side of this district exhibits complex physical feature where this study was carried out within the elevation of 850m to 4300m. The changing elevation gradients along mountain habitats act to control the distribution of butterflies at its ascending range. This study made on different periods in 2009 and 2012 brought a list of 114 species of butterflies from three different destinations of the northern side that included areas like Melamchi, Timbu (central-northern), Helambu (northern) Nakote (north-western) Panch Pokhari and adjoining region (north-eastern). The diversity of butterflies declined gradually above 3500m towards Panch Pokhari whereas species richness was noticed high at 900-2700 m from Melamchi to Helambu route including Nakote, Shermathan and Tarkyghyang. Ecotourism promotional activity can also be linked to the butterfly watch that includes rare and attractive species carrying high interest to the visiting tourists to this region. These tourists intend to watch, document and photograph these butterflies besides birds and other wildlife species. The supplementary information on these insects including other faunal components can be helpful to provide impressive knowledge to the visiting tourists to this part.